1997
DOI: 10.1097/00007890-199705270-00006
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of en Bloc and Single Kidney Transplantation From Very Young Cadaveric Donors1,2,3,4,5,6

Abstract: En bloc transplantation optimizes the outcome of transplantation with very young kidneys. We recommend induction therapy and cyclosporine immunosuppression with cyclosporine levels similar to adult target levels to minimize rejection episodes and, thus, improve outcome. These kidneys should be distributed nationally, because better HLA matching is associated with improved short-term graft survival. Our high ureteral leak rate indicates that alternatives to unstented ureteroneocystostomy should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
81
1
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 33 publications
4
81
1
1
Order By: Relevance
“…Despite this, the number of organs retrieved but not transplanted has increased from 400 in 1990 to 1300 in 2000. Multiple innovative techniques have evolved in an attempt to utilize these wasted organs (5). One of these involves the utilization of double kidney transplants from extremely young or old donors to compensate for marginal allograft function (3).…”
mentioning
confidence: 99%
“…Despite this, the number of organs retrieved but not transplanted has increased from 400 in 1990 to 1300 in 2000. Multiple innovative techniques have evolved in an attempt to utilize these wasted organs (5). One of these involves the utilization of double kidney transplants from extremely young or old donors to compensate for marginal allograft function (3).…”
mentioning
confidence: 99%
“…There were no delayed graft functions in our series. In their series of 22 patients, Satterthwaite et al 1 reported that 14% never functioned, and 23% had delayed graft function.…”
Section: Discussionmentioning
confidence: 96%
“…In their series, Bretan et al 5 documented one graft loss (2.5%) of venous thrombosis due to hypercoagulable state. In their series of 22 en bloc kidney transplants, Satterthwaite et al 1 reported one venous thrombosis (4.5%) and two arterial thrombosis (9%), and all three grafts were lost. In their series of 45 patients, Nghiem et al 7 had six cases of venous thrombosis (13%), and all were lost.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These observations support the use of young donor kidneys into pediatric as opposed to adult recipients since pediatric grafts are better able to acclimatise to the needs of growing children. Although still somewhat contentious, reports, including one using the United Network of Organ Sharing (UNOS) database, suggest an advantage of using of en bloc over single kidneys from young donors [4,[24][25][26].…”
Section: Advantages Of En Bloc Over Solitary Grafts From Young or Idementioning
confidence: 99%